2018
DOI: 10.3389/fchem.2018.00066
|View full text |Cite
|
Sign up to set email alerts
|

Norisoprenoids, Sesquiterpenes and Terpenoids Content of Valpolicella Wines During Aging: Investigating Aroma Potential in Relationship to Evolution of Tobacco and Balsamic Aroma in Aged Wine

Abstract: During wine aging, tobacco and balsamic aroma notes appear. In this paper, volatile compounds directly or potentially related to those aromas have been investigated in Corvina and Corvinone wines during aging. Corvina and Corvinone are two northern-Italy autochthonous red grape varieties, used to produce Valpolicella Classico and Amarone wines, both characterized by tobacco and balsamic aroma notes. Wines were analyzed shortly after bottling or following model aging at 60°C for 48, 72, and 168 h. Volatile comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 51 publications
11
88
0
1
Order By: Relevance
“…Additionally, recent evidence has shown that the molecule can be found in unripe berries of Cabernet Sauvignon and Merlot [119], contributing to the green perception via perceptual interaction with IBMP. A third formation route of 1,8-cineole in wine as product of the reaction of limonene and other terpenols has been also reported [66,121].…”
Section: Aroma Compounds Responsible For Vegetal and Green Aroma And mentioning
confidence: 86%
See 4 more Smart Citations
“…Additionally, recent evidence has shown that the molecule can be found in unripe berries of Cabernet Sauvignon and Merlot [119], contributing to the green perception via perceptual interaction with IBMP. A third formation route of 1,8-cineole in wine as product of the reaction of limonene and other terpenols has been also reported [66,121].…”
Section: Aroma Compounds Responsible For Vegetal and Green Aroma And mentioning
confidence: 86%
“…formed very soon, sharp decrease [15,66] Geraniol Always found; up to 10% of total terpenes in Shiraz, 14% in Muscat [144] No [138]; 3-30% of levels found in enzymatic [12] Maxima in fermentation, sharp decrease in aging [14,143]; formed very soon, sharp decrease [15,66] (Z)-Rose oxide 11-29 ppb in Muscat, depending on maturity [145]; unrelated to free form in raisins [23] 0.04 ppb in Muscat, 0.01 ppb in Grenache; not found in Verdejo, Tempranillo, Chardonnay, Cabernet Sauvignon, or Merlot [12] Geranic acid Up to 2-3 ppm [146,147]; also found in raisins [23]; <4 ppb [145]; up to 7.5% total terpenes in Shiraz, 18% in Muscat [144] Not found [138]; 0.5-50% of levels found in enzymatic [12] 1.5 ppb in Chardonnay juices [148] Piperitone Derived from limonene, unknown accumulation pattern [149]; limonene accumulates in the first periods of aging, then slight decrease [66] n.d.: Not detected. Table 7.…”
Section: Grape Aroma Vs Grape-derived Wine Aromamentioning
confidence: 99%
See 3 more Smart Citations